Evaluative study of the level of quality of services provided by Air Algérie after the Covid-19 crisis - ilhem Chili (Journal of Excellence for Economics and Management Research, 2024)
This study aimed to highlight the importance of service quality in the service sector, and the theoretical aspect was applied to Air Algeria. The importance of the study stems from the importance of the subject itself, as the service is highlighted in its field of use and also determines the institution's field of competition and improves its performance in the market in which it operates. Through this, the problem was formulated as follows: What is the level of quality of services provided by Air Algeria after the Covid 19 crisis?.The study concluded that there is a somewhat high level of improving services and focusing on quality in the company under study. We also recommend the need to pay more attention to the quality of service, quality specifications, and accepting customer suggestions